2015
DOI: 10.1016/j.rpped.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores antropométricos de obesidade na predição de gordura corporal elevada em adolescentes

Abstract: OBJECTIVE: To determine the anthropometric indicators of obesity in the prediction of high body fat in adolescents from a Brazilian State. METHODS: The study included 1,197 adolescents (15-17 years old). The following anthropometric measurements were collected: body mass (weight and height), waist circumference and skinfolds (triceps and medial calf). The anthropometric indicators analyzed were: body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR) and conicity index (C-Index). Body fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 29 publications
3
8
0
11
Order By: Relevance
“…These results corroborate the findings of Pelegrini et al 11 , who investigated adolescents aged 15-17 years of Florianópolis / SC and concluded that of the four anthropometric indicators (BMI, WC, WHtR and C Index), the first three had the highest AUC in relation to high body fat in both sexes. On the other hand, a study conducted in children aged 7-10 years in the same city using the sum of four skinfolds found that BMI had better diagnostic performance in screening excess body fat than WC or WHtR, although the three anthropometric indicators (BMI, WC or WHtR) showed significant AUC values 13 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results corroborate the findings of Pelegrini et al 11 , who investigated adolescents aged 15-17 years of Florianópolis / SC and concluded that of the four anthropometric indicators (BMI, WC, WHtR and C Index), the first three had the highest AUC in relation to high body fat in both sexes. On the other hand, a study conducted in children aged 7-10 years in the same city using the sum of four skinfolds found that BMI had better diagnostic performance in screening excess body fat than WC or WHtR, although the three anthropometric indicators (BMI, WC or WHtR) showed significant AUC values 13 .…”
Section: Discussionsupporting
confidence: 91%
“…In this context, different anthropometric indicators have been used as indirect measure in the identification of adolescents with overweight, high blood pressure and abnormal serum lipemia [9][10][11][12] , which can be considered an important strategy for screening in the school environment because these methods are simple, fast, also allowing referral to a more careful clinical evaluation. Among these indicators, BMI is the most widely used because it is a simple, non-invasive, inexpensive method and has shown good agreement with adiposity indicators 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…etária, crítica para a hipertrofia dos adipócitos. A manutenção da massa corporal e do IMC nesta população de adolescentes obesos pode ser observada como um resultado positivo do nosso estudo 27 . Acreditamos que os voluntários tenham incorporado mudanças comportamentais abordadas no programa bem como a obtenção de conhecimentos fidedignos respaldados por parâmetros científicos para o alcance desses resultados, que para o adolescente obeso isso pode implicar na viabilidade de executar as atividades diárias e representar um efeito protetor contra o desenvolvimento de doenças crônico-degenerativas 28 .…”
Section: Revisões De Literaturaunclassified